1998
DOI: 10.1164/ajrccm.158.6.9802015
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and Cardiovascular Responses to Inspired He-O2 during Exercise in Chronic Obstructive Pulmonary Disease

Abstract: Blunted maximum cardiac output and systemic O2 extraction could constitute primary limits to exercise in severe chronic obstructive pulmonary disease (COPD) or they could simply reflect cessation of exercise because of abnormal pulmonary mechanics. To determine which is the case, eight consecutive patients with severe COPD (FEV1 = 0. 56 +/- 0.04 L, mean +/- SEM), five of whom had alpha1-antiprotease deficiency, performed two incremental cycling tests while breathing N2-O2 or He-O2. Expired gases and V E were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 28 publications
2
56
0
Order By: Relevance
“…This was also seen in patients with different degree of airflow limitation [4]. Whether the oxygen extraction is similar or lower in COPD during exercise [24], these differences cannot account for the decrease in oxygen pulse, since a lower difference would actually magnify the oxygen pulse value. The arterial blood oxygen content is also influenced by the Pa,O 2 , with values ,55 mmHg (,7.3 kPa) decreasing the content and potentially influencing the oxygen pulse results.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This was also seen in patients with different degree of airflow limitation [4]. Whether the oxygen extraction is similar or lower in COPD during exercise [24], these differences cannot account for the decrease in oxygen pulse, since a lower difference would actually magnify the oxygen pulse value. The arterial blood oxygen content is also influenced by the Pa,O 2 , with values ,55 mmHg (,7.3 kPa) decreasing the content and potentially influencing the oxygen pulse results.…”
Section: Discussionmentioning
confidence: 86%
“…Oxygen pulse is a noninvasive and reliable method used to estimate stroke volume and cardiac function [20][21][22][23][24]. The oxygen pulse is calculated by dividing the oxygen uptake (V'O 2 ) by the cardiac frequency (eC), assuming that the arteriovenous difference of oxygen is normal, as appears to be the case in patients with COPD [4,25].…”
mentioning
confidence: 99%
“…Also, we used a non-invasive measure of stroke volume (oxygen pulse), which requires the assumption that the arteriovenous oxygen content difference (Ca,O 2 -Cv,O 2 ) remains constant during exercise. Prior studies of Ca,O 2 -Cv,O 2 during exercise in COPD patients have yielded conflicting results, with some suggesting that extraction is stable during exercise [36,37], whereas others [38] found that oxygen extraction during exercise in COPD is lower than that of normal subjects. Compared with the LVRS group, the non-LVRS group was different in demographics and level of airflow obstruction, but there were no significant differences in baseline static or dynamic lung volumes, which were the physiological measurements of interest in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These properties lead to improved laminar gas flow in the bronchi, resulting in increased oxygenation of the alveoli and decreased carbon dioxide retention. Clinically, this has been reported in several studies as a more rapid fall in PaCO 2 with helium/oxygen mixtures than with conventional therapy (Swidwa et al 1985;Oelberg et al, 1998;Jolliet et al, 1999;Kass and Terregino, 1999;Jaber et al, 2000). In this present study, blood gas analysis was not carried out and, therefore, PaCO 2 values are unknown.…”
Section: Discussionmentioning
confidence: 77%